Effects of Strong Earthquake on Plant Species Composition, Diversity, and Productivity of Alpine Grassland on Qinghai-Tibetan Plateau - Zuo, Hui; Shen, Hao; Dong, Shikui; Wu, Shengnan; He, Fengcai; Zhang, Ran; Wang, Ziying; Shi, Hang; Hao, Xinghai; Tan, Youquan; Ma, Chunhui; Li, Shengmei; et al. (Frontiers in Plant Science, 2022)
Earthquakes occur frequently in fragile alpine grassland areas on the Qinghai-Tibet Plateau (QTP), but few studies have evaluated the impacts of seismo-fault of earthquake on alpine grassland vegetation diversity. In this study, we conducted a field survey of plant communities of alpine grassland along fault zone in the 7.4 Maduo earthquake occured on May 22th, 2021. Surrounding grassland habitat far from the seismo-fault of earthquake was selected as the control. Plant community metrics around and far from seismic rupture was studied. Results showed plant community metrics were negatively affected by seismo-fault of earthquake. Species composition around seismo-fault was being shifted from sedges-dominant into forbs-dominant. And the diversity and aboveground biomass were significantly decreased around seismo-fault compared with the control. Our findings highlighted that earthquakes can cause species loss, plant community shift and finally lead to productivity reduction of alpine grassland. Additionally, forbs may be more competitive than other functional groups after earthquake.